Challenges in Achieving Food Security in India - R Prakash Upadhyay; C Palanivel (Tehran University of Medical Sciences, 2011)
First Millennium Development Goal states the target of "Halving hunger by 2015". Sadly, the recent statistics for India present a very gloomy picture. India currently has the largest number of undernourished people in the world and this is in spite of the fact that it has made substantial progress in health determinants over the past decades and ranks second worldwide in farm output. The causes of existing food insecurity can be better viewed under three concepts namely the: 'traditional  concept' which includes factors such as unavailability of food and poor purchasing capacity; 'socio-demographic concept' which includes illiteracy, unemployment, overcrowding, poor environmental conditions and gender bias; 'politico-developmental concept' comprising of factors such as lack of intersectoral  coordination and political will, poorly monitored nutritional programmes and inadequate public food distribution system. If the Millennium Development Goal is to be achieved by 2015, efforts to improve food and nutrition security have to increase considerably. Priority has to be assigned to agriculture and rural development along with promoting women empowerment, ensuring sustainable employment and improving environmental conditions (water, sanitation and hygiene). As the problem is multi-factorial, so the solution needs to be multi-sectoral.